The logic of collective action for rural warehouse condominiums - Amanda Cristina Gaban Filippi; Patricia Guarnieri; Cleyzer Adrian da Cunha; Alcido Elenor Wander (Logistics, 2022)
Background: Given several bottlenecks in Brazil in distribution logistics, mainly in transport and warehouse activities, some new forms of collective action have appeared. The Condominiums of Rural Warehouses was conceived of to overcome these bottlenecks and provide better income and competitiveness to small producers in agribusiness. This article aims to analyse aspects of collective action with the focus of Rural Condominiums in the context of Brazilian agribusiness. Methods: We conducted exploratory, descriptive and qualitative research under the Theory of Logic of Collective Action lens for this purpose. Besides conducting a literature review, we conducted a semi-structured interview with the managers of the Rural Warehouse Condominiums. We analysed the data through a Categorial Content Analysis. Results: The main results show an approximation of the rural model of the Condominiums of Rural Warehouses with the Theory of Logic of Collective Action, mainly for small producers. Conclusions: We highlight the feasibility of the warehouse structure collectively, as it strengthens and provides greater efficiency to rural business and producers, inserts and integrates the industry into a competitive market environment, provides economic and social benefits, leads to cost reduction, and increased profit. The economic, social and logistical determinants show the product's commercialisation, logistical gains, and the producers' association regarding the development and growth of rural collective action. This paper can be helpful for practitioners and researchers interested in this field.
Keywords: 650; collective action theory of logic; collective actions; rural warehouse condominiums